Tera Gymnastics of the Chinese Ethnic Community in Donggala City: From Physical Action to Social Action - Idrus A.Rore; Lukman Nadjamuddin; Nuraedah (Lembaga Bale Literasi, 2026)
The objectives of this study are: 1) to analyze why Tera Gymnastics in Donggala City is practiced by members of the Chinese ethnic community aged over 50 years; 2) to analyze the motives of the Chinese ethnic community in pioneering and carrying out Tera Gymnastics in Donggala City; and 3) to analyze the typology of social action of the Chinese ethnic community in carrying out Tera Gymnastics in Donggala City. Methodologically, this study employs a qualitative approach with data collection techniques comprising interviews, observation, and documentation. Data analysis was carried out systematically through the stages of data condensation, data display, and conclusion drawing/verification. The findings and discussion of the study reveal: 1) Tera Gymnastics practiced by members of the Chinese ethnic community aged over 50 years in Donggala City can be understood through two approaches, namely a historical approach and a sociological approach; 2) the motives of the Chinese ethnic community in performing Tera Gymnastics in Donggala City are twofold, namely the motive of physical action (health and exercise) and the motive of social action (social motive and togetherness); and 3) the typology of social action of the Chinese ethnic community in carrying out Tera Gymnastics in Donggala City comprises value-rational action and goal-rational action.